2017
DOI: 10.1371/journal.pgen.1006651
|View full text |Cite
|
Sign up to set email alerts
|

A de novo variant in the ASPRV1 gene in a dog with ichthyosis

Abstract: Ichthyoses are a heterogeneous group of inherited cornification disorders characterized by generalized dry skin, scaling and/or hyperkeratosis. Ichthyosis vulgaris is the most common form of ichthyosis in humans and caused by genetic variants in the FLG gene encoding filaggrin. Filaggrin is a key player in the formation of the stratum corneum, the uppermost layer of the epidermis and therefore crucial for barrier function. During terminal differentiation of keratinocytes, the precursor profilaggrin is cleaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Single nucleotide and small indel variants with respect to the CanFam3.1 canine reference genome assembly were called as described (Bauer et al . ). The variants were compared to previously obtained genome sequences.…”
Section: Methodsmentioning
confidence: 97%
“…Single nucleotide and small indel variants with respect to the CanFam3.1 canine reference genome assembly were called as described (Bauer et al . ). The variants were compared to previously obtained genome sequences.…”
Section: Methodsmentioning
confidence: 97%
“…The methodology was previously described (Bauer et al . ). We identified 93 private homozygous and 2339 private heterozygous protein‐changing variants (Table ).…”
mentioning
confidence: 97%
“…Data derived from animal or human models suggest abnormalities in cornification, lipid homeostasis, and keratinocyte adhesion/desquamation among various ichthyoses, implying shared defects in barrier architecture. [18][19][20][21][22][23][24][25][26] Human skin and blood studies have been limited to a few patients or select ichthyosis subtypes and have shown abnormalities in lipid, cornified envelope (CE), and/or other differentiation measures. 18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40] Several observations link ichthyoses, particularly Netherton syndrome (NS), to atopic dermatitis (AD), which is marked by epidermal barrier defects and immune dysregulation.…”
mentioning
confidence: 99%